PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER PADA KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Vetrike Rahayu Sustiasari (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts ability is an important aspect of mathematics learning. But in fact, students’ability to comprehend concepts of mathematics students in VIII grade SMPN 29 Padang is still low. One effort that could be done was applying cooperative learning model numbered head together (NHT) type. Purpose of this study is to know increasing of students’ understanding of mathematical concepts ability who using cooperative learning model NHT type better than conventional learning. Type of research was a quasi experimental research with static group design. Sampling was done by simple random sampling technique. Instrument is final test. Data analysis used Anderson darling test. Based on data analysis, it can be concluded that students’ understanding of mathematical concepts who study by cooperative learning model NHT type is better than conventional learning.Keywords - conventional learning, cooperative learning type NHT, understanding of mathematical concept